Hermeneutika Quraish Shihab dalam Menelaah Ayat-Ayat Gender dalam Tafsir Al-Misbah: Upaya Menemukan Nilai-Nilai Egaliter dalam Al-Qur’an - Muhammad Fakhri Amal; Dzulkifli Hadi Imawan (Jurnal Studi Al-Qur'an, 2025)
The interpretation of Quranic verses concerning gender relations has been a broad topic in Islamic tradition. Many classical interpretations place women in a subordinate position, which in the current context can be considered gender bias. This study aims to analyze the hermeneutical method used by  M. Quraish Shihab to explain gender-related verses in Tafsir al-Misbah. The method used is qualitative with a literature study approach. The results show that  Quraish Shihab applies a hermeneutical approach that considers the social context, historical background, and linguistic meaning in interpreting the verses. Thus, he offers a gender-just perspective on current developments. Verses such as QS. al-Nisa': 34, QS. al-Baqarah: 228, and QS. Al-Baqarah: 282 conservation does not emphasize male dominance but regulates social relations responsive to societal conditions. This interpretation also emphasizes that justice in Islam does not necessarily mean absolute equality but fairness in the rights, responsibilities, and respect for each individual's potential. This research recommends the need for more critical studies of classical interpretations to produce more inclusive and gender-just interpretations.